Formulation and In-vitro Evaluation of Nanovesicles Bilosomes Loaded with Ketoconazole - Lubna Abdalkarim Sabri; Amer Sajjad Khudhair (Iraqi Journal of Pharmaceutical Sciences, 2025)
Ketoconazole (KET), an imidazole derivative with well-known antifungal properties, with poor aqueous solubility, therefore its topical clinical use has practical disadvantages. Bilosome plays an important role in topical drug delivery as they can reduce toxicity and modify dermal drug targeting by acting as a drug reservoir that can adjust the drug release rate.This research aimed to formulate and optimize KET bilosomes to enhance its dissolution and topical antifungal activity. Ten KET bilosomes formulas were prepared by probe sonication method using two types of non-ionic surfactants (Span 40 or Span 60) along with cholesterol and sodium deoxycholate (SDC) as lipid strengthen and bile salt stabilizer, respectively. The formulations were evaluated for vesicles size, PDI, entrapment efficiency and in vitro drug release. The optimum were investigated its morphological property, zeta-potential, FTIR spectrum and antifungal activity.All prepared bilosomes showed nanosize vesicles of (189.27 ± 2.75 - 251.87 ± 1.74 nm) and entrapment efficiency was found in the range of 32.07 ± 0.67 and 92.33± 0.76. The optimum formula that contained span 60: cholesterol: SDC at weight (350:60:15) of spherical shape appearance without aggregation and its zeta potential was – 54.45 mV. The optimum formula was found to provide significant antifungal activity. Its % cumulative KET released was 97% at 8 hours.According to obtained result, it was concluded that bilosomes loaded with KET can be developed successfully to improve dissolution and the antifungal activity.